CONTINUOUS VOCATIONAL EDUCATION: THE LEARNING FOR UNEMPLOYED - Voliarska, O. (Continuing Professional Education: Theory and Practice, 2019)
The paper considers the features vocational learning of the unemployed in the state employment service of Ukraine. Characteristics of modern adult education. The modern adult education, is characterized by interaction with the environment, the internal factors in self-organization, promotes the emergence of educational subsystems and has a conditions for the development of vocational education. The vocational learning for adults realizes subject to their interests and requests, life and professional experience, in the forms of partner’s cooperation of all actors of the educational process. The vocational adult learning is pointed at providing of the common learning process; getting knowledge, skills, abilities; gaining the necessary competencies in joint activities in a simulated reality that provides a high level of motivation to study, in which the participants for themselves find a field to use the acquired experience. The contemporary adult education is characterized by interactions with the environment are the factor of internal self-organization, promote the self-organization, its subsystems and a condition for the evolution of the education system. The vocational learning for unemployed gives the experience of establishing contacts, interdependent ideological and conceptual relations with the world (culture, nature), people and a person himself is the experience of dialogic cognitive activity, social communicative relationships and self cognition. The vocational learning for unemployed careers and occupations that are in demand in the labour market is one of the areas of active employment policy pursued by the State Employment Service of Ukraine. Unemployed, seeking employment in the civil service, specialists assisted in the selection of suitable employment, employment support, involvement in community service, referral to training, retraining and in accordance with the needs of employers and the requirements of the modern labour market.